2017
DOI: 10.1097/wnr.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation induces schizophrenia-like behavior potentially associated with HINT1, NMDA receptor, and dopamine receptor 2

Abstract: Both genetic factors and early life adversity play major roles in the etiology of schizophrenia. Our previous studies indicated that social isolation (SI) during early postnatal development leads to several lasting abnormal behavioral and pathophysiological features resembling the core symptoms of some human neuropsychiatric disorders in mice. The glutamate and dopamine hypotheses are tightly linked to the development of schizophrenia. The cross-talk between glutamate N-methyl-d-aspartate acid receptors and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Frequent sauna baths enhance relaxation, pleasure and well-being, thereby reducing negative feelings and the anxieties and stresses of everyday life, which are also triggers for psychotic symptoms [7][8][9][10]. Sauna bathing is also associated with an opportunity to create friendships, which decrease feelings of isolation, a factor implicated in the development of psychosis [22]. There is evidence suggesting a strong link between elevated hypothalamus-pituitary-adrenal activity and psychosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Frequent sauna baths enhance relaxation, pleasure and well-being, thereby reducing negative feelings and the anxieties and stresses of everyday life, which are also triggers for psychotic symptoms [7][8][9][10]. Sauna bathing is also associated with an opportunity to create friendships, which decrease feelings of isolation, a factor implicated in the development of psychosis [22]. There is evidence suggesting a strong link between elevated hypothalamus-pituitary-adrenal activity and psychosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further, socially isolated mice have been shown to display higher locomotor activity, longer rates of immobility in tail suspension tests, increased adipose mass, and increased voluntary ethanol consumption later in life (Lopez et al, 2011;Sun et al, 2014;Lopez and Laber, 2015;Ieraci et al, 2016). The DA system is significantly impacted by this paradigm, such that following social isolation, mice have demonstrated increased DA-receptor 2 mRNA and protein levels in the NAc, suggestive of excessive dopaminergic activity in mesolimbic areas that are key to motivation and reward salience (Li et al, 2017). Additionally, following social isolation in adolescence, mice show increases in mesolimbic DA-ergic activation in response to cocaine in adulthood, thereby suggesting a long-term impact of social stress on reward sensitivity that persists throughout development (Fosnocht et al, 2019).…”
Section: Social Isolation Paradigmmentioning
confidence: 99%
“…Considering that schizophrenia is often accompanied by dopaminergic system hyperfunction [ 37 ] and the hyperactivity induced by AMPH represents the positive symptom-like behavior in rodent models for schizophrenia [ 38 ], HINT1 KO mice appear to be a useful genetic animal model for studying schizophrenia. Furthermore, we found that HINT1 plays a role in a social isolation (SI) mouse model, characterized by behavioral abnormalities similar to those in schizophrenia, and potential interactions among HINT1, N-methyl-D-aspartate receptor (NMDAR), and DA type 2 receptor (D2R) may underlie the schizophrenia-like behavioral deficits induced by SI [ 39 , 40 ].…”
Section: Hint1 In Neuropsychiatric Disordersmentioning
confidence: 99%